Buttons of San Juan preliminary analysis of buttons recovered from San Juan, Batangas 2009 field season - Basilia, Pauline A. (Hukay, 2014)
Access online through this link: https://journals.upd.edu.ph/index.php/asp/article/view/4368/3964